Social classes and values in Europe - Almeida, J. F.; Machado, F. L.; Costa, A. F. (Portuguese Journal of Social Science, 2006)
Exploiting the analytical potential of the European Social Survey data, this text presents a set of theoretical assumptions and empirical findings concerning class structures, patterns of values and attitudes and the relationship between them. In the first section, a model of analysis is outlined, which relates social dimensions (in this case, classes) with cultural dimensions (in this case, values), both at the individual level and structural level. The second section compares the class composition of the various participating countries and pinpoints common trends and regional specificities. In the third and largest section, several indicators of ideological and political attitudes and electoral practices, as well as Shalom Schwartz's scale of human values, are analyzed in their relationship with the class position of the interviewees.